2007
DOI: 10.1189/jlb.0307174
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-induced neutrophil activation. IX. Syk-dependent activation of class Ia phosphatidylinositol 3-kinase

Abstract: The deposition of monosodium urate (MSU) crystals in the joints of humans leads to an extremely acute, inflammatory reaction, commonly known as gout, characterized by a massive infiltration of neutrophils. Direct interactions of MSU crystals with human neutrophils and inflammatory mediators are crucial to the induction and perpetuation of gout attacks. The intracellular signaling events initiated by the physical interaction between MSU crystals and neutrophils depend on the activation of specific tyrosine kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 49 publications
(67 reference statements)
5
45
0
Order By: Relevance
“…A recent study from our laboratory showed that Syk mediated the MSU crystal-induced activation of class Ia PI3Ks by directly interacting with their regulatory subunit, p85 (39). This interaction was necessary to the subsequent serine/threonine phosphorylation of AKT, a major target of PI3Ks.…”
Section: The Syk-dependent Activation Of Pi3ks By Msu Crystals Dependmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study from our laboratory showed that Syk mediated the MSU crystal-induced activation of class Ia PI3Ks by directly interacting with their regulatory subunit, p85 (39). This interaction was necessary to the subsequent serine/threonine phosphorylation of AKT, a major target of PI3Ks.…”
Section: The Syk-dependent Activation Of Pi3ks By Msu Crystals Dependmentioning
confidence: 99%
“…and the morphological changes in neutrophils characteristic of crystal internalization (47). Syk also mediates the activation of class Ia PI3Ks and regulates several MSU crystal-stimulated neutrophil functions such as degranulation (39). The regulation of the tyrosine phosphorylation cascade initiated by MSU crystals by the serine/threonine kinases of the PKC family (Fig.…”
Section: Syk Is a Substrate Of Pkc In Human Neutrophils Stimulated Bymentioning
confidence: 99%
See 2 more Smart Citations
“…28 To investigate the role of this important cellular sensor, 2 selective pharmacologic inhibitors of PI3K, namely wortmannin and LY294002, were used before pulsing cells with HIV-1. No modulation of virus binding/entry was observed when using both compounds ( Figure 3F for wortmannin and data not shown for LY294002).…”
Section: Src and Syk Family Members Are Involved In The Hiv-1-mediatementioning
confidence: 99%